Licenciatura em matemática : desafios na formação de professores para a educação básica - Silva, Robson Nunes da (2017)
This research has been developed along the Teacher Training and Development line of research, at the stricto sensu Post Graduation Program in Education at the Catholic University in Santos. The topic has emerged from the researcher¿s experience in the classroom, when he saw the difficulties students face while trying to apply Math concepts to IT contents, as well as his role as a manager in a public institution, and while writing the Pedagogical Project for a Math Teaching Undergraduate Program. The aim of this paper was to investigate how Math professors, who teach in undergraduate teaching programs, have dealt with the challenge of training new Math teachers for the Basic Education in Brazil. This is a qualitative research, that has been carried out with both teachers and students, based on the works of Marcelo-Garcia, Pimenta, Gatti among others. In order to carry the investigation, we applied a questionnaire to students who were respectively, on the first, third and fifth terms of two Undergraduate Math Teaching Programs ¿ a private and a public one ¿ in the Metropolitan Region of Baixada Santista in the state of São Paulo, Brazil. Answers have served as a springboard for later, semi-structured interviews with professors in the same programs. Data has brought results about the challenges teacher trainers face, and pointed to relevant questions about their own training, the beginning of their teaching career, not to mention the difficulties they face themselves as teachers. From the analysis of the data, it was possible to reflect upon the situations participants experienced and to understand how they overcome students¿ fragilities as regards to the specific difficulties within the Math area, in order to provide proper training for these students.